ANALISIS PENDAPATAN PEDAGANG PADA OBJEK WISATA DI PULAU AMBON - Azis Laitupa; Hermi Oppier (Jurnal Cita Ekonomika, 2021)
This study aims to identify the factors that influence traders' income on tourism objects in Ambon Island. The research design used was descriptive qualitative research design, which was collected through interviews that in-depth through several key respondents determined using the purposive sampling method on tourist objects, in addition to various other secondary data as a supplement. Production diversity is still lacking, trade service centers are still imperfect, distribution / logistics access, regional openness, economic institutions are not good, access to financial and credit institutions is good, but there must be attention in managerial management, which still needs to be optimized.